Orthosteric and Allosteric Ligands of Nicotinic Acetylcholine Receptors for Smoking Cessation - Mohamed, Tasnim S.; Jayakar, Selwyn S.; Hamouda, Ayman K. (Frontiers in Molecular Neuroscience, 2015)
Nicotine addiction, the result of tobacco use, leads to over six million premature deaths world-wide, a number that is expected to increase by a third within the next two decades. While more than half of smokers want and attempt to quit, only a small percentage of smokers are able to quit without pharmacological interventions. Therefore, over the past decades, researchers in academia and the pharmaceutical industry have focused their attention on the development of more effective smoking cessation therapies, which is now a growing 1.9 billion dollar market. Because the role of neuronal nicotinic acetylcholine receptors (nAChR) in nicotine addiction is well established, nAChR based therapeutics remain the leading strategy for smoking cessation. However, the development of neuronal nAChR drugs that are selective for a nAChR subpopulation is challenging, and only few neuronal nAChR drugs are clinically available. Among the many neuronal nAChR subtypes that have been identified in the brain, the α4β2 subtype is the most abundant and plays a critical role in nicotine addiction. Here, we review the role of neuronal nAChRs, especially the α4β2 subtype, in the development and treatment of nicotine addiction. We also compare available smoking cessation medications and other nAChR orthosteric and allosteric ligands that have been developed with emphasis on the difficulties faced in the development of clinically useful compounds with high nAChR subtype selectivity.